The one-phase SrMg2La2W2O12:Tb3+, Sm3+, Tm3+ phosphor and its optical features in multicolor and white-illumination LEDs - Ha Thanh Tung; Huu Phuc Dang; Phung Ton That (Institute of Advanced Engineering and Science, 2023)
Researchers propose the phosphors emit many colors SrMg2La2W2O12:Tb3+, Sm3+, Tm3+ (SMLLW:RE3+) (RE3+=Tb3+, Sm3+, Tm3+) synthesized using the solid-status reacting technique as promising downward-transformation luminous substances for diodes emit white illumination and screens in the current study. The structural and binding data given by X-ray diffraction (XRD) data and fourier transform infrared (FTIR) spectroscopy suggest the corresponding orthorhombic configuration and vibrational powers, respectively. The stimulation and radiation bands of color of SMLLW:RE3+ phosphor show that such phosphors may be successfully stimulated via ultraviolet (UV) illumination and generate green, orange-red, and blue (stands for G, O-R, B) illumination, in turn. For different doses of the triggers Tb3+, Sm3+, and Tm3+ within the SMLW phosphor base, luminescence, decomposition periods, Commission Internationale De L'eclairage (CIE) color coordination, along with correlated hue heats (Tcct) are specified. When a triple-doped SMLW phosphor is activated using a ligand-to-metal charge transition (LMCT), it produces G, O-R, B hues at the same time and can be adjustable to white light, according to the results. An effective power transfer among rare-earth ions was found and investigated using decay curve analysis. According to the findings, SMLW:RE3+ (RE=Tb, Sm, Tm) are suitable options to use for light-emitting diodes (LEDs) and screens creation.